Effects of central intermittent theta-burst stimulation combined with repetitive peripheral magnetic stimulation on upper limb function in stroke patients (Colombia Medica, 2024)
Background:Intermittent theta-burst stimulation and repetitive peripheral magnetic stimulation can improve motor function in poststroke patients, but the therapeutic effect of this combination remains unclear.Objective:To determine the effects of central intermittent theta-burst stimulation and repetitive peripheral magnetic stimulation on upper limb function.Methods:Fifty-six subacute stroke patients were randomly assigned to three groups: the CMS (n = 18), peripheral magnetic stimulation (PMS) (n = 19) and CPS (n = 19) groups. The CMS group received intermittent theta-burst stimulation and peripheral false stimulation, while the PMS group received repetitive peripheral magnetic stimulation and central false stimulation once a day for five days a week over four weeks. The CPS group received intermittent theta-burst stimulation and repetitive peripheral magnetic stimulation simultaneously once daily for four weeks. The Fugl-Meyer Assessment, Action Research Arm Test, Modified Barthel Index and Modified Ashworth Scale evaluated outcomes before and after four weeks of treatment.Results:The motor function scores of all groups were significantly increased after treatment compared with before treatment, while the Modified Ashworth Scale score showed no significant change. There was a significant difference in the motor function score of the CPS group compared with that of the CMS and PMS groups, but there was no significant improvement in the Modified Ashworth Scale score.Conclusions:Combining the two treatment methods can improve patients' motor function and daily living abilities but cannot improve muscle tone.